2011
DOI: 10.4149/neo_2011_06_507
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of reducing the irradiation dose in regions of active neurogenesis for prophylactic cranial irradiation in patients with small-cell lung cancer

Abstract: Prophylactic cranial irradiation (PCI) is performed on patients with limited or extensive small-cell lung cancer to reduce incidence of brain metastases and prolong survival. PCI may induce neurocognitive impairment. Decreasing irradiation of neural stem cells (NSC) might reduce PCI-induced toxicity. We tested the feasibility of reducing irradiation doses to neural stem cell (NSC) regions while maintaining prescribed doses to the planned target volume (PTV).Irradiation plans utilizing intensity-modulated radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…IMRT has been also proposed for brain metastases treatment. In particular, IMRT has been evaluated in several planning studies, with the aim to spare neural stem cells during WB irradiation, [10][11][12] to treat by stereotactic technique multiple metastases 13 , to simultaneously boost the dose to 2-3 brain metastases during WB 14 and for radiosurgery of multiple brain metastases or large irregular lesions. 15 Furthermore, IMRT has been used in some clinical studies on brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT has been also proposed for brain metastases treatment. In particular, IMRT has been evaluated in several planning studies, with the aim to spare neural stem cells during WB irradiation, [10][11][12] to treat by stereotactic technique multiple metastases 13 , to simultaneously boost the dose to 2-3 brain metastases during WB 14 and for radiosurgery of multiple brain metastases or large irregular lesions. 15 Furthermore, IMRT has been used in some clinical studies on brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently recommended PCI regimen is whole brain irradiation to a total dose of 25 Gy in 10 fractions of 2.5 Gy [48]. It has also been demonstrated that PCI may contribute to the impairment of cognitive functions as a result of post-radiation depopulation of NSCs within the hippocampus [49,50].…”
Section: Clinical Situations In Which Hippocampal Protection Should Bmentioning
confidence: 99%
“…Intensity Modulated Arc Therapy), 77.1% of the IMRT and 42.3% for IMPT (Intensity Modulated Proton Therapy). Tarnawski et al [79] reported that it was possible to achieve a 45% dose reduction when using helical tomotherapy as well as IMRT when planning PCI for 10 patients suffering from small cell lung cancer, whilst still preserving the therapeutic radiation dose to the rest of brain. Similar findings were demonstrated by Gondi et al [80] on five patients when WBRT (30Gy / 10fr) was prescribed using helical IMRT or tomotherapy, where dose levels were respectively reduced by 87% and 81% for the hippocampus.…”
Section: Hippocampal Sparing In Patients Irradiated Electively or Thomentioning
confidence: 99%